O funkcjach syntaktycznych bezokolicznika implikowanego przez verbum finitum - Krupska-Perek, Anna (Acta Universitatis Lodziensis. Folia Linguistica, 1995)
Infinitive implied by verbum finitum may independently function as object or adverbial of purpose or form one of two components of analytic predicate expressing a complex predicate. About 130 verbs can connect with infinitive within the full range of their forms. This large group of structures reveals a considerable internal variety. The above analysis proposes to allocate each time a syntactic function to the infinitive, taking into account semantic syntactic-prosodic, and substitutive criteria. The above criteria allow to ascribe the function of complex verbal predicate to these structures which are characterized by a greater degree of integration, signify a homogenous concrete activity possessing a clear temporal delineation; appear in direct linear connection without a pause, with a single logical accent placed on the infinitive, and have attributes referring to the whole structure. The subordinate clause that might replace them usually contains a formal exponent of modality -by.